Remanufacturing of paper waste for pencil production: a sustainable business assessment - Ziyad Tariq Abdullah (Canadian Science Publishing, 2024)
Large amounts of waste paper are generated annually worldwide. Although some of it is recycled, up to 50% is landfilled or incinerated. The remanufacturing of waste paper to produce pencils is proposed as a novel, sustainable business solution. A sustainability analysis of this process was performed to quantify indexes of technical, environmental, economic, and social sustainability. Small-to-medium business models were evaluated, in which 15 000 pencils/shift/day can be produced from 135 kg of waste paper, with a maximum productivity of 64 800 pencils/day. Productivity, operating costs, power consumption, land footprint, machine delivery cost, and number of workers were used to analyze the technical feasibility. The cost-to-profit ratio, cost and profit per pencil, and daily profit were used to evaluate economic sustainability. The amounts of municipal solid waste and recovered paper waste, saved embodied energy, and prevented CO2 emissions were used to analyze environmental sustainability. The number of workers and labor costs were used to evaluate human development and social sustainability. The machines required for the remanufacturing line are considered sufficiently mature, remanufactured pencils are less expensive to produce than wooden pencils, and the proposed process minimizes the amount of waste paper sent to landfills and avoids the use of new wood for producing pencils, thereby satisfying technical, economic, and environmental sustainability, respectively. The final sustainability index of 0.9 is considered very high and sufficient for operating a profitable, sustainable business with a profit of 252-583 USD/day.